Impact of intense training and rapid weight changes on salivary parameters in elite female Taekwondo athletes - Tsai, M.-L.; Ko, M.-H.; Chang, C.-K.; Chou, K.-M.; Fang, S.-H. (Scandinavian Journal of Medicine & Science in Sports, 2011)
The aim of this study is to examine the cumulative effects of prolonged intensive training with or without rapid weight changes (RWC) on salivary parameters of elite female Taekwondo (TKD) athletes. Ten elite female Taiwanese TKD athletes (ages: 21.3± 1.2 years of age, Ht 164.4 ± 5.6 cm) volunteered to participate in this study. Resting saliva samples were collected at 28-, 14-, 7-, and 1 day before and 1-, 7-, 21 days after a national competition. The levels of salivary immunoglobulin A (sIgA), cortisol, and lactoferrin were measured. In analyzing the anthropometric data, we found that a significant proportion (50%) of elite female TKD athletes had RWC shortly before and after a national competition. The participants were allocated either to the RWC or to the non-RWC group according to their weight change profiles. Our results showed that levels of sIgA and cortisol of athletes with RWC were significantly modulated during the study period. However, athletes without RWC only showed reduced lactoferrin after competition. The results presented here demonstrate that intensive training in combination with RWC affects the mucosal immunity and disrupts the cortisol stress response of elite female TKD athletes.